1990
DOI: 10.1177/172460089000500108
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors in Colorectal Adenocarcinomas and in Other Large Bowel Diseases

Abstract: Seventy-two patients with tumor and ten with non-neoplastic colon disease were studied for the presence of estrogen receptors (ER) by three different methods. Only seven specimens (six primary adenocarcinomas and one recurrent cancer) had an ER concentration above 3 fm/mg of cytosolic protein, with no sex, age and tumor stage correlation. Our results suggest that the large bowel does not contain a cytosolic receptor for estradiol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Some experimental results indicated that estrogen had a trophic effect on colon cancer [1,[11][12] . However, the effect of estrogen on colon cancer is controversial according to some reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some experimental results indicated that estrogen had a trophic effect on colon cancer [1,[11][12] . However, the effect of estrogen on colon cancer is controversial according to some reports.…”
Section: Discussionmentioning
confidence: 99%
“…According to some published reports, ERα was also present in gastric or colon cancer [11][12][13][14][15][16][17][18] . Our results support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry may be of confusion, as CDX2 may be expressed both in endometrioid and mucinous endometrial carcinoma, and ER can occasionally be expressed in colon cancers [12]. PAX8 may help exclude the Mullerian origin; while p16 immunostaining which may help to unmask an endocervical primary, was positive in our case.…”
Section: Discussionmentioning
confidence: 67%